Mediterranean Bioethics in the bioethically lessknown Mediterranean: a struggle for identity - Dorićić, Robert; Buterin, Toni; Eterović, Igor; Gensabella Furnari, Marianna; Giacobello, Maria Laura; Guć, Josip; Kalokairinou, Eleni; Kaluđerović, Željko; Rinćić, Iva; Poljak, Tijana Trako; et al. (Medicina e Morale, 2024)
Primarly as a reponse to mainstream bioethics - the one narrowed-down to issues related to medical ethics and research - various kinds of regional bioethics have emerged in an attempt to incoporate values other than those typical for the Anglo-Saxon culture. Among the most promising ones, the Mediterranean Bioethics, reflecting all the colorfulness of the Mediterranean microcosm and an expanded interest to the entire bios (faithful to the original ideas of Fritz Jahr and Van Renssealer Potter), has found its footholds particularly in Spain, Italy, Croatia, and Greece. Leaving aside those four countries with abundant literature and well-known contributions to the general history of bioethics, we wish to direct attention to other cultures and countries of the Mediterranean region, revealing a more complex struggle for identity.